2020
DOI: 10.3390/biomedicines8090361
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzoylthiamine Has Powerful Antioxidant and Anti-Inflammatory Properties in Cultured Cells and in Mouse Models of Stress and Neurodegeneration

Abstract: Thiamine precursors, the most studied being benfotiamine (BFT), have protective effects in mouse models of neurodegenerative diseases. BFT decreased oxidative stress and inflammation, two major characteristics of neurodegenerative diseases, in a neuroblastoma cell line (Neuro2a) and an immortalized brain microglial cell line (BV2). Here, we tested the potential antioxidant and anti-inflammatory effects of the hitherto unexplored derivative O,S-dibenzoylthiamine (DBT) in these two cell lines. We show that DBT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 63 publications
(128 reference statements)
3
37
0
Order By: Relevance
“…In a rat model of TBI, acute mitochondrial dysfunction due to perturbed function of OGDHC has been corrected by thiamine administration prior to the trauma ( Mkrtchyan et al, 2018b ). Positive action of a precursor of the coenzyme of the 2-oxo acid dehydrogenase complexes, thiamine (vitamin B1), or its pharmacological forms, in patients with neurodegenerative diseases has been reported since a long time ( Blass et al, 1988 ; Costantini et al, 2013 ; Tapias et al, 2018 ; Gibson et al, 2020 ; Sambon et al, 2020 ). Thus, thiamine administration may help prevention of the chronic CNS damage after neurotrauma, which is considered as an essential goal of the current intensive care treatment of patients with CNS injuries ( Stover et al, 2005 ; Vuille-Dit-Bille et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a rat model of TBI, acute mitochondrial dysfunction due to perturbed function of OGDHC has been corrected by thiamine administration prior to the trauma ( Mkrtchyan et al, 2018b ). Positive action of a precursor of the coenzyme of the 2-oxo acid dehydrogenase complexes, thiamine (vitamin B1), or its pharmacological forms, in patients with neurodegenerative diseases has been reported since a long time ( Blass et al, 1988 ; Costantini et al, 2013 ; Tapias et al, 2018 ; Gibson et al, 2020 ; Sambon et al, 2020 ). Thus, thiamine administration may help prevention of the chronic CNS damage after neurotrauma, which is considered as an essential goal of the current intensive care treatment of patients with CNS injuries ( Stover et al, 2005 ; Vuille-Dit-Bille et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have found that chronic treatment with DF402, a bioisostere of Dimebon, an over‐the‐counter drug that demonstrated a mild ability to suppress pathological changes in several models of neurodegenerative diseases, slowed down the development and progression of the disease in S‐FUS[1–359] mice with a statistically significant prolongation effect observed on all three main parameters, namely time to the disease onset (+11%), disease duration (+24%), and animal lifespan (+13%). Although it is difficult to directly compare results of studies that used different experimental setups and endpoints, the efficacy of chronic administration of a low dose of DF402 via drinking water is comparable and possibly higher than the efficacy of a similar protocol of chronic Riluzole administration to S‐FUS[1–359] mice 59–61 . It should be also noted that chronic administration of Dimebon showed a delayed onset of clinical signs and an increase in lifespan of SOD1(G93A) mouse model of ALS, 28 whereas the efficacy of Riluzole in this model was negligible 62 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, BFT and DBT are not disulfides but thioesters. This distinction is very important, because both types of compounds have different pharmacological properties [ 29 , 33 ] and require different pathways for metabolization ( Figure 3 ). Indeed, disulfides require reduction (a redox reaction) by cellular thiols such as reduced glutathione (GSH) or cysteine [ 30 ], while thioesters require hydrolysis to form the open thiamine thiol form.…”
Section: Properties and Mechanism Of Action Of Benfotiaminementioning
confidence: 99%
“…However, as most analytical methods are based on the detection of fluorescent thiochrome derivative, only BFT metabolites with an intact thiazolium ring are detected [ 33 ]. Other metabolites would require the use of mass spectrometric detection [ 29 , 33 , 37 , 38 ]. Hence, the existence of presently unknown metabolites of BFT cannot be excluded (see also Figure 3 ).…”
Section: Properties and Mechanism Of Action Of Benfotiaminementioning
confidence: 99%
See 1 more Smart Citation